Molecular modeling, synthesis, and evaluation of 1-(4-methoxybenzofuran-5-yl)-3-phenylpropane-1, 3-dione for its anxiolytic potentiality - P Ayash Kumar, Sanjita Das, Sradhanjali Mohapatra, Saumya Priya Basu, Kalicharan Sharma, Monika Sharma, Aniruddh Pratap Singh (Journal of Applied Pharmaceutical Science, 2020)
The disabling mental illness anxiety is gradually affecting the modern society in any age group worldwide. The search for novel bioactive entity from herbal origin for different disorders has become the center of attraction significantly from the past few decades. Gamma-aminobutyric acid (GABA) is the primary inhibitory neurotransmitter known to be responsible for the anxiolytic activity of most of the potent anxiolytic agents. All the available data of pongamol 1-(4-methoxybenzofuran-5-yl)-3-phenylpropane-1, 3-dione (MPD) were based on natural or semi-synthetic source. The synthetic routes were using easily available source and quick, cost-effective, and high yielding process. MPD has traditionally been acquired from natural sources mainly from the extracts of fruits of Pongamia pinnata and Pongamia glabra, where the yield value and the yield time are the main drawbacks. Keeping in view of the above aspects in the present research, it was approached to synthesize and evaluate the anxiolytic potential 1-(methoxybenzofuran-5yl)- 3-phenylpropane-1, 3-dione on experimental animals and docking procedure after its synthesis. The study of MPD on the gross behavior of mice showed a significant Central Nervous System (CNS) depressant effect. Furthermore, its anxiolytic activity was confirmed by observing its reduced locomotion of mice using actophotometer and elevated plus-maze apparatus. The highest docking score was observed to be −3.22 than the diazepam (−3.21) against Gamma Amino Butyric Acid-A (GABAA). The present study provides a promising anxiolytic agent, MPD, which has its potency due to the GABAA receptor binding and causing the mitigation of the symptoms of anxiety.
Keywords: MPD, gross behavior, anxiolytic, molecular modeling, GABAA receptor.